A Comparative Study of “yīlái…èrlái…” in Chinese and “ประการแรก...ประการที่สอง ...” in Thai - Chatsanguthai, Chatsaran (Journal of Sinology (วารสารจีนวิทยา), 2014)
There are some similarities and differences between “yīlái…èrlái…” in Chinese and “ประการแรก...ประการที่สอง ...” in Thai. In terms of meanings and functions they are basically the same, “yīlái…èrlái…” and “ประการแรก... ประการที่สอง...” both stated reasons, aims or conditions of matters or things. However, there are some differences too. For example, the ways to state reasons, aims or conditions in Thai are more flexible than in Chinese, “ประการแรก” can be matched with other words while “yīlái” cannot. In Chinese, “yīlái…èrlái…” can be replaced with “yīzé…èrzé…” “yīzhě…èrzhě…” and “yī zé…zài zé…”, often used in written language while “yīlái…èrlái…” and “yīlái…yīlái…” often used in spoken language. “ประการแรก...ประการที่สอง...” in Thai can be used in both spoken and written language.